The Role of West Java Islamic Organizations in Determining the Direction of Political Policy in West Java (Case Study of the Persatuan Ummat Islam Organization) - Muhamad Ma’sum (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of democracy in Indonesia has been marked by the increasing role of non-state actors in political processes, including religious-based mass organizations. From the perspective of political science, religious organizations constitute an integral part of civil society and possess the capacity to influence public policy through social and moral legitimacy. West Java, as a province with a strong religious and social base, represents a strategic arena for the activities of Islamic organizations, one of which is Persatuan Ummat Islam (PUI). This study aims to analyze the role of the Islamic organization PUI in shaping the direction of political policy in West Java. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, document analysis, and observation. The findings indicate that PUI functions as a non-formal political actor by engaging in policy advocacy, political communication, and the construction of public moral discourse. These findings confirm that Islamic mass organizations constitute an important element of local democracy in Indonesia.